2001
DOI: 10.1093/jn/131.12.3277
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Fortification Increases Red Blood Cell Folate Concentrations in the Framingham Study

Abstract: In 1996 the Food and Drug Administration (FDA) issued a regulation to take effect in January 1998 that all enriched cereal grain products include 140 microg of folic acid/100 g. The present cross-sectional study was undertaken to assess the effect of this fortification on RBC folate concentrations in the Framingham Offspring Cohort. Among those who did not take B-vitamin supplements, we compared RBC folate in 561 individuals who were examined before implementation of the FDA mandatory folic acid fortification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 19 publications
11
50
0
1
Order By: Relevance
“…However, the mean erythrocyte folate concentrations of our subjects were much higher than the data from NHANES III (Ganji & Kafai, 2003), whereas the values were comparable with those in other studies carried out in USA and Canada prior to fortification as well as in Denmark and Korea where not exposed to fortification (House et al, 2000;Rasmussen et al, 2000;Choumenkovitch et al, 2001;Ahn et al, 2002). Homocysteine concentrations in our study were lower than those reported in UK, Canada, Netherlands and USA, (Bates et al, 1997;Ray et al, 2000;de Bree et al, 2001;Jacques et al, 2001), but were similar to the values (6.4-7.6 mmol/l) reported in Korea by other investigators (Lee et al, 1998(Lee et al, , 2000.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the mean erythrocyte folate concentrations of our subjects were much higher than the data from NHANES III (Ganji & Kafai, 2003), whereas the values were comparable with those in other studies carried out in USA and Canada prior to fortification as well as in Denmark and Korea where not exposed to fortification (House et al, 2000;Rasmussen et al, 2000;Choumenkovitch et al, 2001;Ahn et al, 2002). Homocysteine concentrations in our study were lower than those reported in UK, Canada, Netherlands and USA, (Bates et al, 1997;Ray et al, 2000;de Bree et al, 2001;Jacques et al, 2001), but were similar to the values (6.4-7.6 mmol/l) reported in Korea by other investigators (Lee et al, 1998(Lee et al, , 2000.…”
Section: Discussionsupporting
confidence: 86%
“…This was followed in Canada and Chile. In these countries, folic acid fortification resulted in the increase in folate consumption and circulating folate concentration in the general population, and the reduction of neural-tube defects (Jacques et al, 1999b;Choumenkovitch et al, 2001;Green, 2002;Ray et al, 2002;Hertrampf et al, 2003;Quinlivan & Gregory, 2003). There are still concerns about possible adverse effects such as masking symptoms of vitamin B 12 deficiency among those who consume synthetic folic acid in excess of the Tolerable Upper Intake level of 1.0 mg per day (Rader 2002;Rampersaud et al, 2003;Shane, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the previously identified role for nutritional status in homocysteine metabolism, 18,72 and is consistent with the beneficial effects of folate fortification. 73 We further observed that the mean plasma folate concentration for this study population was very low (3.8 and 3.4 ng/ml for men and women, respectively). A level of 3 ng/ml has often been used as a cutoff for inadequate folate status.…”
Section: Discussionsupporting
confidence: 47%
“…This has resulted in Homocysteine and dementia increased levels of serum folic acid and of RBC folate in the entire population. 56 The effects of these increases on homocysteine levels in the elderly population are largely unknown, but interesting data have started to emerge. A Chilean study recently reported that folic acid fortification of flour had a moderate lowering effect on homocysteine levels in the elderly population (mean age 74.3 years).…”
Section: Effects Of Folic Acid Fortification Of Grain Productsmentioning
confidence: 99%